Student teachers character development in teacher education institutes: a review - Ismail Mohamed; Soaib Asimiran; Shafee Mohd Daud; Shamsuddin Ahmad (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia, 2015)
Teachers are the role models of character education in schools and as such student teachers during their training period should be educated to possess the required characteristics of effective teachers. This article reviews the contexts of character education and teacher character development programs, focusing on the elements of good character development training, and drawing experiences from practices in several developed countries. Challenges in character education are also highlighted in the discussions. It is suggested that teacher training institutes should pay serious attention particularly in the development of effective teachers during their training period in teacher education institutes.